Fracture analysis on thin rotating disc with radial cracks - Wong, Jun Kiat (Nanyang Technological University, 2024)
Thin rotating disc are sub-components that is typically used within the industrial machinery. Numerical analysis using boundary element method (BEM) was utilised on a thin rotating disc with peripheral holes that are subjected to both rotational and centrifugal forces. Normalised stress concentration ( ) and stress intensity factor ( ) were calculated and obtained. In the stress concentration analysis, the maximum principal stress was found to be in the region around the edge of the slot. In the analysis of stress intensity, a crack depth of 0.7 is observed to have the highest stress intensity. Geometrical parameters are varied, and it is found that stress concentration factors and stress intensity factors reduce as the number of slots increases.